Penerapan Program Penguatan Pendidikan Karakter Dan Literasi Di SD Negeri 034 Bengkulu Utara - I Gusti Ngurah Teja (IJOCE: Indonesia Journal of Civic Education, 2020)
The purpose of this study was to see how the implementation of strengthening character education integrates with literacy in SD Negeri 034 Bengkulu Utara. The method in this research is descriptive qualitative research. The results of the research on the implementation of strengthening character and literacy education were carried out at SD Negeri 034 Bengkulu Utara through integration in every activity, which has been stated in the curriculum so that all programs will be monitored and have a clear measure of success. The conclusion of the development of the Strengthening Character Education (PPK) and Literacy program at SD Negeri 034 Bengkulu Utara was carried out starting from habituation activities, learning, extracurricular programs, national and religious holidays and library management. Keywords: School Literacy, Character Strengthening Program